Legal Protectıon Of Credıtors As Collateral Owners For Auctıons Wıth Cıvıl Lawsuıts (Case Study Of Decısıon Number 743/PDT. G/2021/PN JKT. BRT) - William Mulyadanika; Mella Ismelina F.R (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Law is a coercive regulation, which determines the calculation of human practice within the scope of society made by the official body of the authorities, which violation of the regulation results in the taking of action, namely with certain laws. To ensure the continuity of the balance in the relationship between members of the community, a legal regulation is needed, where any violation of the law will be subject to punitive sanctions. In order to maintain the rule of law, it can continue and be accepted by the community and must be in accordance with and must not conflict with the principle of justice, namely the purpose of the law to ensure legal certainty in society and the law must be based on justice. In meeting the daily needs of life, it requires the interaction of each individual in trying where every business needs a capital while not all entrepreneurs have enough capital to grow their business. Through financial institutions themselves, namely human banks, they can find solutions by borrowing capital used for business. In making a loan, there is a dependent right that is used as collateral for the debt. After making achievements or paying debt repayment obligations, no one knows about the upcoming circumstances such as natural disasters which will cause the credit to become bad. So that the guaranteed dependent rights will be the auctioned goods to relieve the debt. So that when conducting an auction the bank as the money lender will receive money from the winner of the auction, but the borrower of the money has applied for a credit extension and did not get a warning letter or some from the bank so that the borrower of money or debtor filed a civil lawsuit against the bank, namely the creditor, and what are the rights of the debtor, creditor and winner of the auction